Evaluating the use of sustainable approaches for reducing river flooding and erosion in the Upper Trusan River, Sarawak - Lip, Yih Yoong (2024)
This thesis summarises work undertaken to address flooding and erosion problems in the upper part of the Trusan catchment, Sarawak, Malaysian Borneo (hereafter the ‘Upper Trusan’). The Upper Trusan has been experiencing severe flooding and associated riverbank erosion, both of which affect rice production. This work aimed to identify and evaluate options for reducing the risk and impacts of these phenomena using sustainable ‘green’ approaches. I assessed the suitability of different types of riverbank protection measures (brush walls, brush mattresses, bamboo fencing and geotextile mattresses) as short-term measures for reducing erosion in some of the worst affected areas. In addition, we evaluated opportunities for managed flooding to help reduce flood peaks and attenuate flood waves in the downstream areas. I also assessed the contribution that land use management (especially the conservation of forest cover) could play in minimising flood risk under future land cover scenarios.